Associations of TFEB Gene Polymorphisms With Cognitive Function in Rural Chinese Population - Wei, Yanfei; Liu, Shuzhen; Cai, Jiansheng; Tang, Xu; Zhang, Junling; Xu, Min; Liu, Qiumei; Wei, Chunmei; Mo, Xiaoting; Huang, Shenxiang; Lin, Yinxia; Mai, Tingyu; et al. (Frontiers in Aging Neuroscience, 2021)
Background: The study aimed to investigate the relationship between transcription factor EB (TFEB) gene polymorphisms, including their haplotypes, and the cognitive functions of a selected population in Gongcheng County, Guangxi. Methods: A case-control study approach was used. The case group comprised 339 individuals with cognitive impairment, as assessed by their Mini-Mental State Examination scores; the control population also comprised 339 individuals who were matched by sex and age (±5 years) in a 1:1 ratio. TFEB gene polymorphisms were genotyped in 678 participants (190 men and 488 women, aged 30–91 years) by using the Sequenom MassARRAY platform. Results: Multifactorial logistic regression analysis showed that in the dominant model, the risk of developing cognitive impairment was 1.547 times higher in cases with the TFEB rs14063A allele (AG + AA) than in those with the GG genotype (adjusted odds ratio [OR] = 1.547, Bonferroni correction confidence interval = 1.021–2.345). Meanwhile, the presence of the TFEB rs1062966T allele (CT + TT) was associated with a lower risk of cognitive impairment in comparison with the presence of the CC genotype (adjusted OR = 0.636, Bonferroni correction confidence interval = 0.405–0.998). In the co-dominant model, the risk of developing cognitive impairment was 1.553 times higher in carriers of the TFEB rs14063AG genotype than in carriers of the GG genotype (adjusted OR = 1.553, Bonferroni correction confidence interval = 1.007–2.397). After the Bonferroni correction and adjustment for confounding factors, the association of TFEB rs1062966 with cognitive function persisted in the analyses stratified by education level. Ethnically stratified analysis showed a significant association between TFEB rs1062966 and cognitive function in the Yao population. The multilocus linkage disequilibrium analysis indicated that the identified single nucleotide polymorphisms were not inherited independently. The haplotype analysis suggested that the rs14063A–rs1062966C–rs2278068C–rs1015149T haplotype of the TFEB gene increased the risk of cognitive impairment (P < 0.05) and that the rs14063G–rs1062966T–rs2278068C–rs1015149C haplotype was associated with a reduced risk of cognitive impairment (P < 0.05). Conclusions: TFEB rs1062966 polymorphisms and their rs14063A–rs1062966C–rs2278068C–rs1015149T and rs14063G–rs1062966T–rs2278068C–rs1015149C haplotypes are genetic factors that may affect cognitive function among the rural Chinese population.